2013
DOI: 10.1111/sdi.12129
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Return to Dialysis in Patients with Failing Kidney Transplants

Abstract: In the last decade, the number of patients starting dialysis after a failed kidney transplant has increased substantially. These patients appear to be different from their transplant‐naïve counterparts, and so may be the timing of dialysis therapy initiation. An increasing number of studies suggest that in transplant‐naïve patients, later dialysis initiation is associated with better outcomes. Very few data are available on timing of dialysis reinitiation in failed transplant recipients, and they suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Ojo et al [15] reported 5-year patient survival after primary renal allograft failure was 36, 49, and 65% for type I diabetes mellitus (DM), type II DM, and non-diabetic ESRD patients, respectively ( p < 0.001; DM vs. non-diabetics). Close monitoring and management of comorbid disease is essential for risk reduction in these patients [7,9]. The most common causes of death in our study included cardiac and infectious diseases, which is consistent with the current literature [16,17,18,19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Ojo et al [15] reported 5-year patient survival after primary renal allograft failure was 36, 49, and 65% for type I diabetes mellitus (DM), type II DM, and non-diabetic ESRD patients, respectively ( p < 0.001; DM vs. non-diabetics). Close monitoring and management of comorbid disease is essential for risk reduction in these patients [7,9]. The most common causes of death in our study included cardiac and infectious diseases, which is consistent with the current literature [16,17,18,19].…”
Section: Discussionsupporting
confidence: 80%
“…Allograft failure is often due to rejection, drug toxicity, and chronic allograft nephropathy [8]. Graft failure and return to dialysis (RTD) confers a greater mortality risk than in transplant-naive patients starting dialysis [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in the USA 30% and 15% of patients transition to dialysis with an eGFR of 10 to <15 and ≥15 mL/min/1.73 m 2 , respectively [9]. However, very few if any patients ever transition to RRT with an eGFR >25 mL/min/1.73 m 2 ( Figure 2) [11]. Although several studies have questioned the wisdom of premature dialysis initiation [12], it remains unknown as to when the best timing for ESRD transition should occur for individuals, i.e.…”
Section: M Po R Ta N C E O F S T U Dy I N G T R a N S I T I O N S Imentioning
confidence: 99%
“…across different age groups or comorbid conditions or race/ethnicities, in order to achieve the best ESRD survival and other outcomes. There are a number of key unanswered questions related to the transition of care in CKD [11,13]. For instance, there is an urgent need to examine whether the transition to RRT and the type and modality of the transition should be selected based on pre-dialysis patient data.…”
Section: M Po R Ta N C E O F S T U Dy I N G T R a N S I T I O N S Imentioning
confidence: 99%
“…(6,11) The risk for death or recipient's return to dialysis after graft failure is higher compared with those on the waiting list for dialysis. (12) Studies have evaluated different strategies to identify nonadherence, including pill counts, self-report, collateral effect register, laboratory analyses of immunosuppressive drug levels, and electronic monitoring. This last is considered the gold standard for identifying adherence to immunosuppressive therapy but is not always viable because of its high cost.…”
Section: Introductionmentioning
confidence: 99%